Arweck, E. and Stringer, M. D., "Theorizing Faith: The Insider/Outsider Problem in the Study of Ritual" - Flanagan, Kieran (Quaker studies, 2004)
Arweck, E. and Stringer, M.D. eds., Theorizing Faith: The Insider/Outsider Problem in the Study if Ritual, Birmingham: University of Birmingham Press, 2002. pp. vi + 186, ISBN 1-902459-33-4, Paper, £19.95.